Analisis Efektifitas Pembelajaran Daring Terhadap Hasil Belajar Pendidikan Olahraga Pada Masa Pandemi Covid-19 SMK SMTI Bandarlampung - Cahyo Pratomo; Aditya Gumantan (Journal of Physical Education, 2021)
AbstractThis research is intended to reveal the process of online learning in Sports subject during Covid-19, whether it affects the results of learning process or it does not give any effects. It applies the method of Descriptive Statistics Qualitative. The subjects of this research are Vocational High School’s students in Bandar Lampung. In this research, the students are given questionnaires related to learning process that have three indicators, learning planning, process, and evaluation. The results of the questionnaires show that 15% students totally agree, 53% students agree, 24% students half agree, 6% students do not agree, and 2% students do not totally agree with the learning planning. Meanwhile, the results show that 10% students totally agree, 50% students agree, 31% students half agree, 7% students do not agree, and 2% students do not totally agree with the learning process. In the meantime, the results of the questionnaires show that 13% students totally agree, 63% students agree, 22% students half agree, 1% students do not agree, and 1% students do not totally agree with the learning evaluation.  Keywords : Students, Learning Process, Sports Education